Spinal Muscular Atrophy Types, Innovations in Diagnosis and Treatment - Hatice Tankisi; Aycan Ünalp (Galenos Publishing House, 2023)
Spinal muscular atrophy (SMA) is a severe condition with recent advancements in diagnosis and treatment. Its prevalence might be higher than anticipated in countries, where consanguineous marriages are common, implying that there could be cases of prenatal deaths. It is crucial for pediatricians to be familiar with the various forms of SMA that exhibit different symptoms and to promptly refer patients to pediatric neurology to ensure timely treatment and prevent complications. Without treatment, decreased levels of survival motor neuron (SMN) protein can result in disability and even death, ranging from functional motor impairments to muscle weakness and respiratory failure. Clinically, the severity of SMA varies significantly depending on the loss of lower motor neurons, ranging from prenatal forms to adult-onset forms, leading to progressive muscle weakness and atrophy. Homozygous deletion of the SMN1 gene is responsible for approximately 95-98% of SMA cases. A SMN2 gene closely related to SMA can partially compensate for the loss of SMN1, with disease severity correlating with the number of copies. For patients who cannot receive intrathecal treatment with nusinersen, due to spinal deformities like advanced scoliosis, risdiplam may serve as an alternative treatment option. We eagerly await the publication of long-term results of the studies for patients who have received multiple treatments in some way. Future research will potentially identify more cost-effective and easily measurable biomarkers. It is crucial to enhance pediatricians' awareness of this disease, as early treatment can yield promising outcomes.